2008
DOI: 10.1111/j.1937-8327.2000.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Fluency Training and Accuracy Training on Application and Retention

Abstract: The effects of fluency training on the acquisition and retention of a composite skill were compared with those of training to accuracy only. Participants were 30 college students, and the task was a stimulus equivalence task, similar to the one used by Binder (1995) in earlier assessments. Participants learned associations between Hebrew symbols and nonsense syllables and between nonsense syllables and Arabic numerals. Immediately after training and every 2 or 4 weeks for 16 weeks, they were tested on a compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…A number of research studies to date have demonstrated the attainment of fluent performances as a result of frequency-building with mathematics skills (Hartnedy et al, 2005;Poncy, et al, 2010). Further, the attainment of fluent performances with component mathematics skills has been associated with improvements in endurance (Brady & Kubina, 2010;McDowell & Keenan, 2001) and application (Bucklin et al, 2000;Cavallini & Perini, 2009;Chiesa & Roberston, 2000;Kubina et al, 2004) as well as overall mathematical ability (Carr & Alexeev, 2011;Carr et al, 2008 …”
Section: Purpose Of the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of research studies to date have demonstrated the attainment of fluent performances as a result of frequency-building with mathematics skills (Hartnedy et al, 2005;Poncy, et al, 2010). Further, the attainment of fluent performances with component mathematics skills has been associated with improvements in endurance (Brady & Kubina, 2010;McDowell & Keenan, 2001) and application (Bucklin et al, 2000;Cavallini & Perini, 2009;Chiesa & Roberston, 2000;Kubina et al, 2004) as well as overall mathematical ability (Carr & Alexeev, 2011;Carr et al, 2008 …”
Section: Purpose Of the Present Studymentioning
confidence: 99%
“…Kubina and Yurich (2012) describe application as the ability to apply one or more element behaviors or pre-requisite skills to more complex behaviors or skills once a specific frequency with those skills is achieved (e.g., the ability to recognise or read letters at a high frequency will result in an improvement in applying this skill to decoding full words). A number of studies to date have demonstrated the ability of fluency-based instruction to improve participants' application of fluent skills to more complex tasks (Bucklin, Dickinson, & Brethower, 2000;Cavallini & Perini, 2009;Chiesa & Roberston, 2000;Kubina, Young, & Kilwein, 2004). However, continued research is necessary in order to further evaluate the occurrence of this outcome as a consequence of fluency-based instruction across behavioral repertoires.…”
Section: The Findings From the 2009 Program For International Assessmentmentioning
confidence: 99%
“…The FT group's higher scores in the composite test offer preliminary evidence consistent with this view. In addition, the FT group retained their greater application of knowledge at follow-up, suggesting that more fluent component skills may aid retention in both component and composite skills (Binder 1993;1996;Bucklin et al, 2000).…”
Section: Fluency With Behaviour Support Plans 17mentioning
confidence: 99%
“…In one study, Bucklin, Dickinson and Brethower (2000) compared the effects of fluency training with accuracy training alone on college students' ability to retain and apply learned component skills in an untrained composite task. Findings demonstrated that fluency training produced a higher number of correct responses per minute (rate) for component and composite skill performance, both immediately after training, and after a 16-week follow-up.…”
Section: Fluency With Behaviour Support Plansmentioning
confidence: 99%
“…We focused on response rates because a growing literature (e.g., Binder, 1996;Bucklin, Dickinson, & Brethower, 2001;Kubina & Wolfe, 2005) suggests that procedures that promote fluency can promote important learning outcomes, such as retention (i.e., appropriate, high-rate behavior persists long after training is completed), endurance (i.e., appropriate, high-rate behavior persists for durations greater than the durations of practice sessions), application (i.e., behavior can easily combine with other behaviors to form composites), and adduction (i.e., behaviors combine to form new behavior with little or no additional instruction). Presumably, procedures that produce many fluent editing skills could help editors easily eliminate previously encountered and novel stylistic problems, long after training (Binder, 2004; see the discussion of fluency by Johnson & Layng, 1996).…”
mentioning
confidence: 99%